Development of an Inclusive E-Learning Platform for Visually Impaired Students - Oyekunle, Rafiat Ajibade; Chukwura, Henry Chukwunonso; Talpur, Noureen; Balogun, Abdullateef Oluwagbemiga (Studies in Learning and Teaching, 2024)
This research focuses on developing an inclusive e-learning platform to enhance accessibility for visually impaired students, addressing shortcomings in conventional learning environments. The primary aim is to create an educational space that is more accommodating and supportive of diverse user needs. The platform prioritizes user-friendliness, offering essential features such as language translation and support for multimodal content, including text and video formats. The development process employed the Rapid Application Development (RAD) methodology, enabling iterative prototyping and seamless integration of user feedback. This approach facilitated continuous refinement of the platform to meet real user needs effectively. The design adhered strictly to W3C accessibility guidelines, ensuring compliance with global web accessibility standards. Technologies like HTML, CSS, PHP, and JavaScript were utilized, alongside accessibility testing tools such as non-visual desktop access (NVDA) and WAVE, to ensure a robust and accessible user experience. Key features, including font size and contrast adjustment sliders, were integrated based on user feedback. The results indicate that the platform significantly enhances the accessibility of educational resources, empowering visually impaired students. Its novel combination of RAD methodology and strict adherence to accessibility standards demonstrates a practical and user-centered approach to tackling educational inequities.